Fatores determinantes da distribuição de plantas submersas e dos atributos das assembléias de macrófitas aquáticas no reservatório de Rosana. - Pierini, Sandra Andréa (2005)
The effects of underwater radiation, represented by different depths (0.5 and 1.0m) and the effects of stands colonized by E. najas and E. densa upon the growth rates of shoots and roots, stem number and length and ratio root:shoots of these species were assessed in field experiments in the Rosana Reservoir. Differences in the measurements were not significant when species grew at 0.5 and 1.0m, indicating that these two underwater radiation levels did not affect the measured attributes. Nevertheless, there were significant differences between species and the results for all attributes were higher for E. najas than E. densa. The effect of stands showed significant differences for shoot:root ratios, root growth rates and number of branches. The interaction between species branches number and stands were also significant. E. najas showed lower value of the shoot:root ratios when growing inside stands of E. densa. It is probably a response to maximize the use of underwater radiation. On the other hand, E. densa increased allocation of biomass to roots, probably to maximize nutrient uptake. Despite different strategies, the values of all attributes were greater in E. najas than E. densa, mainly when the first species grew inside stands of its own species. Based upon these results, we suppose that E. najas is a more efficient competitor when both colonize simultaneously the same habitat.